2010
DOI: 10.1111/j.1365-3083.2009.02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of TLR2 and TLR4 in Human Neutrophil Functions AgainstParacoccidioides brasiliensis

Abstract: In paracoccidioidomycosis, a systemic mycosis caused by the fungus Paracoccidioides brasiliensis (Pb), studies have focused on the role of neutrophils that are involved in primary response to the fungus. Neutrophil functions are regulated by pro‐ and anti‐inflammatory cytokines. The molecular mechanisms involved in this process are not fully understood, but there are strong evidences about the involvement of toll‐like receptors (TLR). We aimed at evaluating TLR2 and TLR4 expression on human neutrophils activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 53 publications
3
15
0
Order By: Relevance
“…Using immunofluorescence microscopy, we verified that the absence of TLR-2 and TLR-4 leads to impaired conidial phagocytosis ( Figure 1F and Supplementary Figure 2). Similar results were seen in P. brasiliensis (51,52) and Sporothrix brasiliensis (53,54) infection. In contrast, in C. albicans and A. fumigatus infection, TLR-4 does not play a crucial role in the phagocytic process (55,56).…”
Section: A B D E Csupporting
confidence: 85%
“…Using immunofluorescence microscopy, we verified that the absence of TLR-2 and TLR-4 leads to impaired conidial phagocytosis ( Figure 1F and Supplementary Figure 2). Similar results were seen in P. brasiliensis (51,52) and Sporothrix brasiliensis (53,54) infection. In contrast, in C. albicans and A. fumigatus infection, TLR-4 does not play a crucial role in the phagocytic process (55,56).…”
Section: A B D E Csupporting
confidence: 85%
“…The increase in phagocytosis promoted by ArtinM may be related to the high production of cytokines, such as TNF-α and IFN-γ by these cells when in the presence of the lectin ( Figures 1 , 2 , 4 , 5 ). In fact, several authors have reported the importance of cytokines in the activation of phagocytic cells and killing of P. brasiliensis yeast ( Cano et al, 1992 ; Moscardi-Bacchi et al, 1994 ; Calvi et al, 2003 ; Carmo et al, 2006 ; Rodrigues et al, 2007 ; Acorci-Valério et al, 2010 ). Similar to ArtinM, a plant lectin, natural components, such as propolis, have been shown to improve the fungicidal activity of macrophages against P. brasiliensis ( Murad et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…PMN from infected patients may inactivate Pb [ 36 ] and are considered important as immune attack cells that contribute to the host response against this fungal infection, especially in the early stages of PCM [ 37 ]. Nevertheless, neutrophil functions such as fungal killing require activation by cytokines and other elements of the immune system [ 37 ]; IFN-γ, TNF-α, granulocyte-macrophage colony-stimulating factor (GM-CSF) and IL-15 are some examples of factors that can activate human neutrophils to carry out increased fungicidal activity by a mechanism dependent on production of ROS such as H 2 O 2 and superoxide anion [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%